Economic and monetary integration in East Asia - Ahmad, Nursilah; Duasa, Jarita (USIM Press, Universiti Sains Islam Malaysia, 2019)
Economic integration (or union) refers to economic linkages or interdependence between countries. The flow of trade, capital, labor and technology across countries are evidence of economic linkages. The reduction or elimination of trade barriers among nations will eventually bring together the commodity market, financial market and labor market of the economies involved. However, the dissimilarity of the level of economic development and monetary system is commonly said to be the main obstacle to the adoption of policies to support economic and monetary integration. On the other hand, the similarity of past macroeconomic policies, stage of economic development and financial systems would increase the suitability of countries to be integrated. This paper examines the latest trend in the economic and monetary integration in selected East Asia countries and look for possible convergence pattern. There are evidence supporting positive impact of forming an economic and monetary integration in these economies.